2018
DOI: 10.13005/ojc/340270
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Alkaloid Compounds from Litsea cubeba Lour

Abstract: Litsea cubeba (Lour.) heartwood. was extracted by maceration. Ethanol extract was fractionated with liquid-liquid extraction using n-hexane, chloroform at pH 3, 7, 9 and 11 to obtained alkaloid fractions. Isolation of alkaloid compounds were isolated with preparative thin layer chromatography. Antioxidant activity for fractions and isolates were determined with DPPH and ABTS assay. The highest IC 50 were given by chloroform fractions at pH 7 and compound III. They IC 50 were 23.81 ± 0.01; 3.12 ± 0.02 µg/mL for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
(21 reference statements)
1
20
0
3
Order By: Relevance
“…Diabetes is a state of increased free radical production that elicits oxidative stress as a consequence of an imbalance between radicalgenerating and radical-scavenging systems [3]. The uncontrolled production of oxygen free radicals and the unrateable system of antioxidant capability in protection results in the cause of many diseases, such as cancer, diabetes, heart diseases, Alzheimer's, and ageing [23]. Higher levels of HbA1c cause complications.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a state of increased free radical production that elicits oxidative stress as a consequence of an imbalance between radicalgenerating and radical-scavenging systems [3]. The uncontrolled production of oxygen free radicals and the unrateable system of antioxidant capability in protection results in the cause of many diseases, such as cancer, diabetes, heart diseases, Alzheimer's, and ageing [23]. Higher levels of HbA1c cause complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, these fractions demonstrated lower ABTS scavenging ability than the control, vitamin C (IC50 = 13.50 µg/mL). Dalimunthe et al 24 reported higher IC50 values for alkaloid fractions of L. cubeba. Similarly, H2O2 scavenging activity also increased in a dosedependent manner (Figure 2a), with the stem alkaloid fraction scavenging 55.66% and 80.42% of H2O2 at 20 µg/mL and 100 µg/mL, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Antioxidant activity Numerous findings agree that diseases such as cancer, diabetes, cardiovascular and neurodegenerative disorders are exacerbated by oxidative stress arising from the inability of the body to completely scavenge ROS, which damage biological molecules including lipids, proteins and deoxyribonucleic acid (DNA). [19][20][21][22][23][24] Despite the availability of synthetic antioxidants such as butylated hydroxy anisole (BHA) and butylated hydroxy toluene (BHT), there is increased search for natural antioxidants as these are considered to be safer, cheaper and less toxic. The antioxidant activity of alkaloid fractions of T. hirtum was evaluated by various in-vitro models including the DPPH, ABTS, H2O2 radical scavenging activity, reducing power and metal chelating activity.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were analyzed using a FACScan flow cytometer. On the basis of DNA content, the percentage of cells in each stage in the cell cycle (G 1 , S, and G 2 /M) was calculated using ModFit Lt. 3.0 s [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%